Thermal and crystallization kinetics of yttrium‐doped phosphate‐based glasses. (27th November 2019) - Arafat, Abul; Samad, Sabrin A.; Wadge, Matthew D.; Islam, Md Towhidul; Lewis, Andrew L.; Barney, Emma R.; Ahmed, Ifty
Abstract: Yttrium‐doped glasses have been utilized for biomedical applications such as radiotherapy, especially for liver cancer treatment. In this paper, the crystallization behavior of phosphate‐based glasses doped with yttrium (in the system 45P2 O5 –(30 −  x ) Na2 O–25CaO– x Y2 O3 —where x  = 0, 1, 3 and 5) have been investigated via Differential Scanning Calorimetry (DSC) using nonisothermal technique at different heating rates (5°C, 10°C, 15°C and 20°C/min). The glass compositions were characterized via EDX, XRD, Density and Molar volume analysis. The Moynihan and Kissinger methods were used for the determination of glass transition activation energy ( E g ) which decreased from 192 to 118 kJ/mol (Moynihan) and 183 to 113 kJ/mol (Kissinger) with increasing yttrium oxide content. Incorporation of 0 to 5 mol% Y2 O3 revealed an approximate decrease of 71 kJ/mol (Ozawa and Augis) for onset crystallization ( E x ) and 26 kJ/mol (Kissinger) for crystallization peak activation energies ( E c ). Avrami index ( n ) value analyzed via Matusita–Sakka equation suggested a one‐dimensional crystal growth for the glasses investigated. SEM analysis explored the crystalline morphologies and revealed one‐dimensional needle‐like crystals. Overall, it was found that these glass formulations remained amorphous with up to 5 mol% Y2 O3 addition with further increases in Y2 O3 content resulting in significant crystallization.